Retention analysis from vitrified low-activity waste and simulants in a laboratory-scale melter. Issue 5 (1st March 2022) - Dixon, Derek R.; Hall, Mark A.; Lang, Jesse B.; Cutforth, Derek A.; Stewart, Cody M.; Eaton, William C.
Abstract: The Waste Treatment and Immobilization Plant (WTP) will process and stabilize nuclear waste stored in tanks on the Hanford Site. At the WTP, the tank waste will be combined with glass-forming chemicals to make a melter feed slurry that can be vitrified in joule-heated melters. Technetium-99 ( 99 Tc), a long-lived radionuclide present in tank waste, is semi-volatile from a glass melt at elevated temperatures. A small laboratory-scale melter system has been designed by PNNL to operate under radioactive conditions, giving it the ability to vitrify actual tank waste and gain information about melter feed processability and the partitioning of components of interest. This study describes two runs performed in a duplicate system with non-radioactive simulants of Hanford tanks 241-AP-107 and 241-AN-105 to gain insight into the relationship between the retentions of 99 Tc and its non-radioactive surrogate Re while also investigating the effects of increasing the reducing agent such as sucrose during vitrification on processing and the retention of semi-volatile components in the glass product. The results from these runs align with the general trends of greater retention in the glass of Re compared to 99 Tc and the improved retention in the glass of Re with increased reducing agent.